Pharmacokinetics, pharmacodynamics and safety of QGE031 (ligelizumab), a novel high‐affinity anti‐IgE antibody, in atopic subjects. Issue 11 (November 2014) - Arm, J. P.; Bottoli, I.; Skerjanec, A.; Floch, D.; Groenewegen, A.; Maahs, S.; Owen, C. E.; Jones, I.; Lowe, P. J.
Summary Background Using a monoclonal antibody with greater affinity for IgE than omalizumab, we examined whether more complete suppression of IgE provided greater pharmacodynamic effects, including suppression of skin prick responses to allergen. Objective To explore the pharmacokinetics, pharmacodynamics and safety of QGE031 (ligelizumab), a novel high‐affinity humanized monoclonal IgG1κ anti‐IgE. Methods Preclinical assessments and two randomized, placebo‐controlled, double‐blind clinical trials were conducted in atopic subjects. The first trial administered single doses of QGE031 (0.1–10 mg/kg) or placebo intravenously, while the second trial administered two to four doses of QGE031 (0.2– 4 mg/kg) or placebo subcutaneously at 2‐week intervals. Both trials included an open‐label omalizumab arm. Results Sixty of 73 (82%) and 96 of 110 (87%) subjects completed the intravenous and subcutaneous studies, respectively. Exposure to QGE031 and its half‐life depended on the QGE031 dose and serum IgE level. QGE031 had a biexponential pharmacokinetic profile after intravenous administration and a terminal half‐life of approximately 20 days. QGE031 demonstrated dose‐ and time‐dependent suppression of free IgE, basophil FcεRI and basophil surface IgE superior in extent (free IgE and surface IgE) and duration to omalizumab. At Day 85, 6 weeks after the last dose, skin prick wheal responses to allergen were suppressed by > 95% and 41% in subjects treated subcutaneously with QGE031 (2 mg/kg) or omalizumab, respectively (P < 0.001). Urticaria was observed in QGE031‐ and placebo‐treated subjects and was accompanied by systemic symptoms in one subject treated with 10 mg/kg intravenous QGE031. There were no serious adverse events. Conclusion and Clinical Relevance These first clinical data for QGE031, a high‐affinity IgG1κ anti‐IgE, demonstrate that increased suppression of free IgE compared with omalizumab translated to superior pharmacodynamic effects in atopic subjects, including those with high IgE levels. QGE031 may therefore benefit patients unable to receive, or suboptimally treated with, omalizumab.